New insights into correlated materials in the time domain—combining far-infrared excitation with x-ray probes at cryogenic temperatures. (9th July 2021) - Mankowsky, Roman; Sander, Mathias; Zerdane, Serhane; Vonka, Jakub; Bartkowiak, Marek; Deng, Yunpei; Winkler, Rafael; Giorgianni, Flavio; Matmon, Guy; Gerber, Simon; Beaud, Paul; Lemke, Henrik Till
Abstract: Modern techniques for the investigation of correlated materials in the time domain combine selective excitation in the THz frequency range with selective probing of coupled structural, electronic and magnetic degrees of freedom using x-ray scattering techniques. Cryogenic sample temperatures are commonly required to prevent thermal occupation of the low energy modes and to access relevant material ground states. Here, we present a chamber optimized for high-field THz excitation and (resonant) x-ray diffraction at sample temperatures between 5 and 500 K. Directly connected to the beamline vacuum and featuring both a Beryllium window and an in-vacuum detector, the chamber covers the full (2–12.7) keV energy range of the femtosecond x-ray pulses available at the Bernina endstation of the SwissFEL free electron laser. Successful commissioning experiments made use of the energy tunability to selectively track the dynamics of the structural, magnetic and orbital order of Ca2 RuO4 and Tb2 Ti2 O7 at the Ru (2.96 keV) and Tb (7.55 keV) L -edges, respectively. THz field amplitudes up to 1.12 MV cm −1 peak field were demonstrated and used to excite the samples at temperatures as low as 5 K.